2020
DOI: 10.3390/v12080899
|View full text |Cite
|
Sign up to set email alerts
|

Oral Infection by Mucosal and Cutaneous Human Papillomaviruses in the Men Who Have Sex with Men from the OHMAR Study

Abstract: Both mucosal and cutaneous Human Papillomaviruses (HPVs) can be detected in the oral cavity, but investigations regarding the epidemiology of cutaneous HPVs at this site are scarce. We assessed mucosal (alpha) and cutaneous (beta and gamma) HPV infection in oral samples of HIV-infected and uninfected men who have sex with men (MSM). Oral rinse-and-gargles were collected from 310 MSM. Alpha HPVs were detected using the Linear Array, whereas beta and gamma HPVs were detected using multiplex PCR and Luminex techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
2
11
1
Order By: Relevance
“…Data about the prevalence of oral infection by alpha, beta, and gamma HPVs in the same groups of HIV-infected and uninfected MSM included in the present study have been previously presented and discussed [6]. Briefly, we found that oral HPV prevalence rates in our participants exceed those observed in non-MSM and other populations, possibly because of different demographic characteristics (e.g., age and ethnicity) and sexual behavior.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Data about the prevalence of oral infection by alpha, beta, and gamma HPVs in the same groups of HIV-infected and uninfected MSM included in the present study have been previously presented and discussed [6]. Briefly, we found that oral HPV prevalence rates in our participants exceed those observed in non-MSM and other populations, possibly because of different demographic characteristics (e.g., age and ethnicity) and sexual behavior.…”
Section: Discussionmentioning
confidence: 59%
“…Regarding beta and gamma HPVs, the use of a type-specific assay with a wide capacity to detect multiple genotypes certainly may have contributed to the higher prevalence for these HPVs. Moreover, the prevalence rates observed for the three genera at oral level differed from those assessed at anal level, as already discussed [6,16].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Previously, we investigated anal and oral HPV infections in MSM populations, and compared HIV-infected vs. HIV-uninfected subjects in terms of prevalence at the two sites [14,15]. Therefore, the comparison between HIV-infected and HIV-uninfected MSM will not be further discussed here.…”
Section: Discussionmentioning
confidence: 99%